Comparison Between Clinicopathological Characteristics, BRAF V600E and TERT Promoter Mutation of Familial Non-Medullary Thyroid Carcinomas, and Sporadic Case - Yang, Tian; Huang, Longsheng; Chen, Chang; Luo, Han; Jiang, Yong (Frontiers in Oncology, 2021)
Background It has been debated whether familial non-medullary thyroid carcinoma (FNMTC) is more aggressive and has a worse prognosis than sporadic non-medullary thyroid carcinoma (SNMTC). Our aim was to compare the invasiveness and prognosis of FNMTC and SNMTC by their biological behavior and molecular changes. Method and Material Our group mainly compared 106 patients with FNMTC whom have complete clinicopathological data during 2011–2019 in West China Hospital, Sichuan University, and 212 randomly selected cases with SNMTC were included to compare their biological behavior, recurrence and mortality, and molecular expression of BRAF V600E and TERT promoter. At the same time, FNMTC cases were divided into four subgroups, namely, two affected members group, three or more affected members, parent/offspring group, and sibling group, and they were compared with SNMTC separately to analyze the difference in their invasiveness and prognosis. Results We found that the mean tumor size of FNMTC (0.96 ± 0.53cm) was smaller than that of SNMTC (1.15 ± 0.72 cm) (p = 0.020), while no significant difference in the incidence of other clinicopathological factors, including bilateral growth, capsular invasion, with thyroid nodular goiter or not, multifocality, lymph node metastasis, extrathyroidal extension, iodine 131 treatments, T stage, and American Joint Committee on Cancer (AJCC) stage, was observed between FNMTC and SNMTC (p > 0.05), between each FNMTC subgroup (p > 0.05), and between each FNMTC subgroup and SNMTC (p > 0.05). There was no significant difference in recurrence, mortality, and BRAF V600E and TERT promoter mutation between FNMTC and SNMTC, among which 50/60 (83.33%) of FNMTC patients had BRAF V600E mutation and 1/32 (3.13%) had TERT promoter mutation, while the mutation rates of SNMTC were 93/108 (86.11%) and 3/64 (4.69%) (p > 0.05). Conclusion There was no significant difference in invasiveness and prognosis between FNMTC and SNMTC by biological behavior, patient survival, and molecular level comparison.